TANGGUNG JAWAB PRODUSEN BAHAN BAKAR MINYAK DAN INDUSTRI OTOMOTIF ATAS KEBIJAKAN NET ZERO EMISSION(STUDI : KEBIJAKAN BAKU MUTU EMISI GAS BUANG KENDARAAN BERMOTOR TIPE BARU) - Vikram Surya Husada, (2022)
This study is to analyze the Government's policy regarding the responsibility of the Oil Fuel Producers and the Automotive Industry on the Net Zero Emission Policy. The problem in this research is to find out the sanctions and also legal comparisons with other countries related to the responsibility of Oil Fuel Producers and the Automotive Industry to protect the environment. In this study using a normative juridical method. The results of the research obtained are that in this case, producers of fuel oil and also the automotive industry must follow the applicable technical regulations so that they are not only concerned with business aspects but also must pay attention to aspects of environmental sustainability because the energy and automotive sectors are sectors that contribute to carbon emissions. largest and can cause air pollution. Because when there is pollution, many of the rights of citizens to get clean and healthy air are disturbed. It is necessary to establish a special regulation to immediately implement the use of New and Renewable Energy so that the Net Zero Emission target can be implemented in accordance with the Government's Strategic Plan